Prominent Actors Among The Bollywood Film Industry - Dr. A. Abdul Rasheed (International Journal of Advanced Science and Technology, 2020)
The people are interacting with other people for their various needs and as a matter of social concern. They need to interact with the other people to construct a social network. The film industry has a lot of people like actor, actress, writer, director, musician to name a few. The industry has so many cast acted in so many movies over the period of time. They may sometimes long-lasting or they may not survive in the industry due to various reasons behind it. The problem of identifying the prominent person in the film industry is an interesting one. The Bollywood industry in India is one among the oldest one in the country and also it produced so many popular actors and actress in the last decades. This research is focused on identifying prominent persons, the actors and/or actresses, from the Indian Hindi Cinema industry. In support of finding the solution, a dataset with the movie details over a period is considered for the study. The measures of social network analysis are applied over the dataset and the results are discussed as part of the research.